FAMILY INFLUENCE ON EATING HABITS AND LIFESTYLE DEVELOPMENT IN CHILDHOOD (Revista Contexto & Saúde, 2020)
Objective: To analyze the family influence on eating habits and lifestyle development in children. Methods: In this study participated 100 children and their respective relatives (100). The data were collected from a questionnaire and anthropometric evaluation. The study population corresponds to the total number of students, aged 2 to 12 years old, from two municipal schools where the research took place. Results: Most children (57%) presented eutrophic, but the overweight and obesity number was relevant. Both children and their families use a lot of digital technology. The family showed influence on the number of children's meals, fruit consumption, vegetables and sweets, and physical activity, as well as learning about healthy eating. Conclusion: The family members influence on eating habits and lifestyle development in childhood, but the school is an important place to promote healthy eating.
Keywords: Food consumption; Exercise; Culture; Child Nutrition